Effectiveness of a Nature-Based Virtual Reality Intervention on Preoperative Anxiety among First-Time Major Surgery Patients: A Quasi-Experimental Study - Farama, Dodi Aflika; Gani, Abdul; Wibowo, Wahyu Dwi Ari (Journal of Applied Nursing and Health, 2026)
Background: Major surgery is frequently associated with high levels of preoperative anxiety, which can negatively affect physiological stability and postoperative recovery. Despite evidence supporting the effectiveness of nature-based virtual reality (VR) therapy in reducing anxiety in high-income settings, its applicability in low- and middle-income countries (LMICs), particularly district hospitals, remains unclear. This study aimed to evaluate the effectiveness of nature-based VR therapy in reducing preoperative anxiety among first-time major surgery patients. Methods: This study employed a quasi-experimental pre-test–post-test control group design, reported in accordance with the TREND guideline. A total of 104 adult patients scheduled for first-time elective major surgery were recruited using consecutive sampling and equally allocated to an intervention group (n=52) and a control group (n=52). The independent variable was nature-based VR therapy, and the dependent variable was preoperative anxiety. Anxiety was measured using the State Anxiety subscale of the State–Trait Anxiety Inventory (STAI), a validated instrument with good reliability (Cronbach’s α = 0.83). The intervention group received a single 5-minute nature-based VR session 20–30 minutes before surgery, while the control group received standard preoperative care. Data were analyzed using paired and independent t-tests, and effect size was calculated using Cohen’s d. Results: Participants were predominantly aged 46–60 years (39.4%), equally male and female, mostly classified as ASA II (69.2%), and commonly scheduled for abdominal surgery (40.4%). The intervention group showed a significant anxiety reduction (mean difference = −16.10; p < 0.001; Cohen’s d = 1.98), whereas the control group showed no significant change (−2.38; p = 0.062). Post-intervention anxiety scores were significantly lower in the VR group than in the control group (t = 9.074; p < 0.001; Cohen’s d = 1.78). Conclusion: Nature-based VR therapy is an effective, nurse-led, non-pharmacological intervention for reducing preoperative anxiety in first-time major surgery patients. Integration of VR into routine preoperative nursing care may enhance patient-centered care and support anxiety management in resource-limited hospital settings.